2020
DOI: 10.3389/fmicb.2020.00613
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Moonmilk of Baeg-nyong Cave, Korean CZO

Abstract: The Baeg-nyong cave is a limestone cave which has been nominated as the first critical zone observatory (CZO) in South Korea. Moonmilk is a well-known speleothem composed of various carbonate minerals. To characterize moonmilk from the Baegnyong cave, we performed mineralogical analyses and applied high-throughput 16S rRNA gene sequencing to analyze the microbial communities, including bacteria and fungi, of dry and wet moonmilk samples. The results showed that the dry and wet moonmilk samples had different an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Actinobacteria and Proteobacteria are the two most dominant phyla in caves [31,41], and a large number of actinobacterial genera were retrieved in different caves, either as isolates, clones or Next Generation Sequencing (NGS) studies. Interestingly, most of the genera and families reported in this study were also found by Gonzalez-Pimentel et al [15] and Gonzalez-Pimentel [37] in different lava tubes from La Palma Island.…”
Section: Microbial Communitiesmentioning
confidence: 99%
“…Actinobacteria and Proteobacteria are the two most dominant phyla in caves [31,41], and a large number of actinobacterial genera were retrieved in different caves, either as isolates, clones or Next Generation Sequencing (NGS) studies. Interestingly, most of the genera and families reported in this study were also found by Gonzalez-Pimentel et al [15] and Gonzalez-Pimentel [37] in different lava tubes from La Palma Island.…”
Section: Microbial Communitiesmentioning
confidence: 99%
“…2). Fungi display a tight homeostatic control of the cytoplasmic Ca 2+ concentration as it regulates the apical growth of the hyphae and participates in several vital intracellular processes such as development and proliferation, stress response and integrity of the cell wall [50,51]. Calcium homeostasis by fungi occurs mainly in three ways: (i) the active and passive transport of Ca 2+ -ions in/out of the cell (Ca 2+ pumped ), (ii) the sequestration of cytoplasmic Ca 2+ into specific organelles (Ca 2+ organelles ) and (iii) binding to calmodulins (CaM) and calcineurins (Ca 2+ proteins ) [50].…”
Section: Mechanisms Of Fungal Biomineralization Relevant For the Application Of Self-healing Concretementioning
confidence: 99%
“…Calcium homeostasis by fungi occurs mainly in three ways: (i) the active and passive transport of Ca 2+ -ions in/out of the cell (Ca 2+ pumped ), (ii) the sequestration of cytoplasmic Ca 2+ into specific organelles (Ca 2+ organelles ) and (iii) binding to calmodulins (CaM) and calcineurins (Ca 2+ proteins ) [50]. The pumping is performed by specific channels and antiporters fine-tune the intracellular calcium concentration [51]. Ca 2+ -ATPase are transporters capable of sequestering calcium and directing it to different organelles, such as vacuoles, Golgi and ER, decreasing cytosolic calcium levels [51].…”
Section: Mechanisms Of Fungal Biomineralization Relevant For the Application Of Self-healing Concretementioning
confidence: 99%
See 2 more Smart Citations